Perbandingan Tingkat Kesegaran Jasmani Siswa Sekolah Menengah Atas Negeri 1 Sungai Beremas Kabupaten Pasaman Barat Dengan Siswa Sekolah Menengah Atas Negeri 11 Padang - mukhtadi radifan; ishak aziz (Jurnal Patriot, 2019)
The purpose of this study was to get a real picture of the level of physical fitness of each student in the school and at the same time to see the differences in the level of physical fitness of their students. This type of research is komperasi, with planning research "Ex Post Facto". The population in this study were all students of the 1 Berangan River Middle School in West Pasaman Regency and Padang 11 High School Middle School students. Samples taken in class XI using Random sampling technique. Thus the number of samples is 25 male students of SMA Beremas 1 High School in West Pasaman Regency and 20 male students of Padang 11 High School. Then the data obtained were analyzed using the statistic formula "t test". From the results of data analysis obtained tcount (2.13) <ttable (1.68), meaning that there is a significant difference between the level of physical fitness of the students of Negeri 1 Sungai Beremas Middle School with Padang 11 High School Middle School students. Based on the average value, it was obtained that the average of the Middle School 1 Sungai Beremas High School students was 17.72, much different from the average of the 11 High School Students of Padang, which was 15.85. This proves that the physical fitness level of the Sungai Beremas 1 High School Middle School students is better than the Padang 11 High School Middle School students in other words the hypothesis in this study is accepted.